Determinants of device success after transcatheter aortic valve replacement in patients with type-0 bicuspid aortic stenosis - Xiao, Zhicheng; Yao, Jing; Liu, Xinmin; Yuan, Fei; Yan, Yunfeng; Luo, Taiyang; Wang, Moyang; Zhang, Hongliang; Ren, Faxin; Song, Guangyuan (Frontiers in Cardiovascular Medicine, 2023)
Background: Clinical evidence of transcatheter aortic valve replacement in patients with type-0 bicuspid aortic valve was relatively scarce.Aims: Our goal was to explore determinants of device success after transcatheter aortic valve replacement in patients with type-0 bicuspid aortic valve morphology.In this retrospective multicenter analysis, we included 59 patients with symptomatic severe aortic stenosis with type-0 bicuspid aortic valve morphology who underwent transcatheter aortic valve replacement. Type-0 bicuspid aortic valve was identified with multidetector computed tomography scans. The technical success rate was 89.8%, and the device success rate was 81.4%. Patients were divided into a device success group and a device failure group according to Valve Academic Research Consortium-3 criteria.Results: When we compared the two groups, we found that the ellipticity index of the aortic root and the presence of bulky calcifications at the commissure were statistically different (ellipticity index 35.7±1.7 vs. 29.7±1.1, p=0.018; bulky calcification at the commissure, 54.5% vs. 4.5%, p<0.001). Further multivariate logistic analysis showed that bulky calcification at the commissure had a negative correlation with device success (odds ratio 0.030, 95% confidence interval 0.003-0.285, p=0.002). Yet there was no statistical correlation between the ellipticity index and device success (odds ratio 0.818, 95% confidence interval 0.667-1.003, p=0.053). 2 This is a provisional file, not the final typeset article Conclusions: The presence of bulky calcifications at the commissure is negatively correlated with device success after transcatheter aortic valve replacement in patients with type-0 bicuspid aortic valve.